The Brussels effect : how the European Union rules the world - Bradford, Anu (New York, NY : Oxford University Press, 2019)
'The Brussels Effect' offers a novel account of the EU by challenging the view that it is a declining world power. Anu Bradford explains how the EU exerts global influence through its ability to unilaterally regulate the global marketplace without the need to engage in neither international cooperation nor coercion.
Due to be issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 20, 2019).
Keywords: European Union; European Union -- Influence; Trade regulation; Globalization; Hegemony; Law; International law